Enhancing gain of dual band antenna for Wi-Fi/WiMAX applications using array technique - Taha Sediq, Hiwa (International Journal of Engineering and Technology, 2018)
This study describes the design of dual rectangular microstrip patch antenna for Wi-Fi and WiMAX wireless communication applications. In this work, the technique of design array patch antennas was used in order to improve the physical antenna characteristics for Wi-Fi and WiMAX device. As a result, the proposed technique causes to increase the gain and directivity of the antenna. Using this method also leads to enhance measurement bandwidth of antenna and some other antenna parameters as mentioned in this research paper. A dual-band microstrip patch antenna is developed for WiMAX/Wi-Fi wireless applications that operate at a minimum frequency of 2.4 GHz and a maximum frequency band of 3.5 GHz with its dimensions is L= 88.27 mm, W= 171.4 mm and h= 1.67 mm. The achieved parameters of dual patch array antenna for 2.4 GHz and 3.5 GHz are (gain of 8.25 dB, directivity of 10.4 dBi, measurement bandwidth of 65.82 MHz and measurement return loss of -20.86 dB) and (gain of 7.56 dB, directivity of 8.76 dBi, measurement bandwidth of 98.96 MHz and measurement return loss of -21.38 dB) respectively.Â
Keywords: Dual Patch Array Antenna; Gain; WIMAX; Reflection Coefficient; Inset Feed Technique; Radiation Pattern.